Exploring implicit cognition : learning, memory, and social cognitive processes - Jin, Zheng, 1984-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book explores research surrounding the ways in which an individual's unconscious is able to influence and impact that person's behavior without their awareness, focusing on topics pertaining to social cognition and the unconscious process"--Provided by publisher.
Applying the IAT to assess big five personality traits: a brief review of measurement and validity issues / Francesco Dentale, Michele Vecchione, Claudio Barbaranelli -- Priming / Christina Bermeitinger -- Individual differences in implicit learning: current problems and issues for research / Daisuke Nakamura -- Rethinking Bloom's taxonomy: implicit cognitive vulnerability as an impetus towards higher order thinking skills / Caroline M. Crawford, Marion S. Smith -- Implicit social cognition and language attitudes research / Andrew J. Pantos -- Implicit processes and emotions in stereotype threat about women's leadership / Gwendolyn A. Kelso, Leslie R. Brody -- Smoking, implicit attitudes, and context-sensitivity: an overview / Sabine Glock, Ineke M. Pit ten-Cate -- Function over form: a behavioral approach to implicit attitudes / Anthony G. O'Reilly, Bryan Roche, Aoife Cartwright -- The role of implicit mechanisms in buffering self-esteem from social threats / Jordan B. Leitner, Chad E. Forbes -- How social factors influence implicit knowledge construction on the internet / Albena Antonova -- Hidden curriculum determinants in (pre)school institutions: implicit cognition in action / Lucija Jancec, Sanja Tatalovic Vorkapic, Jurka Lepicnik Vodopivec -- Unraveling a progressive inquiry script in persistent virtual worlds: theoretical foundations and decision processes for constructing a socio-cultural learning framework / Nikolaos Pellas.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 01/10/2015).
Keywords: Cognition; Implicit learning; Implicit memory; Social perception; Brain mechanisms; Human cognitive system; Implicit measures; Implicit-explicit relations; Electronic books